MEDB-51. Impact of residual tumor on outcomes in children and adolescents with medulloblastoma in the German HIT-cohort. (3rd June 2022) - Wolgast, Stella; Obrecht, Denise; Mynarek, Martin; Bison, Brigitte; Schwarz, Rudolf; Pietsch, Torsten; Kortmann, Rolf-Dieter; Warmuth-Metz, Monika; Rutkowski, Stefan
Abstract: INTRODUCTION: To date, a historical threshold of 1.5cm 2 extent of resection (EOR) of the primary tumor is used for risk stratification in pediatric medulloblastoma (MB). METHODS: Data of n=348 patients with MB included into the German HIT-MED studies and registries from 2000-2017 were retrospectively analyzed. Kaplan-Meier statistics and Cox regressions were calculated to determine the influence of EOR, histological and molecular subtype, MYC/N-amplification and presence of metastases at first diagnosis on overall and progression-free survival (OS/PFS). ROC curves were calculated aiming at identifying a new EOR cut-off. RESULTS: Median age at diagnosis was 6.8 [0.1-20.5] years. After initial surgery, residual tumor (R) ≥1.5cm 2 was present in 129/348 patients (37%). 57% presented with additional metastases. In most cases, classic histology was found (71%, DMB/MBEN: 20%, LC/AMB: 9%). Molecular subtype was nonWNT/nonSHH in 68% (Group 4: 37%, Group 3: 31%), WNT in 6% and SHH-activated types in 26% of evaluated cases (n=208). MYC/MYCN-amplification was present in 5 and 4%, respectively. 41/348 patients received additional surgery, resulting in 73% GTR (not reported: n=22). EOR had no significant impact on OS/PFS (GTR: 5y-OS/PFS 69.9±3.4/57.6±3.7%, STR: 5y-OS/PFS 71.4±4.1/56.2±4.5%, p=0.6/0.8; Cox: p=0.2/0.4; median follow-up 8.4 [0.1-18.0] years). ROC curves did not identify a significantly improved limit for outcome-relevant EOR cut-off. Analyses confirmed less favorable OS/PFS for patients with metastatic disease (p=0.04/p<0.05), LC/AMB (p<0.05/p<0.05), Group 3 (p<0.05/p<0.05), and MYC-amplification (p<0.05/p<0.05). Cox regression confirmed an increased risk for Group 3 (OS: HR=4.74, p<0.05, PFS: HR=2.90, p<0.05) and M+ (PFS: HR=2.69, p<0.05). DISCUSSION: No distinct influence of EOR </≥1.5cm 2 on OS/PFS in pediatric MB was detected. The relevance of EOR and the historical limit of 1.5cm 2 should be further investigated in distinct MB subtypes and in context of other risk factors.